Web theory : an introduction - Burnett, Robert, 1956- (Routledge, 2003)
Web Theory is a comprehensive and critical introduction to the theories of the internet and the world wide web. Robert Burnett and P. David Marshall examine the key debates which surround internet culture, from issues of globalisation, political economy and regulation, to ideas about communication, identity and aesthetics. Web Theory explore the shifts in society, culture and the media which have been brought about by the growth of the world wide web. It identifies significant readings, web sites and hypertext archive sources which illustrate the critical discussion about the internet and it m.